The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1097/ta.0b013e318265cec2
|View full text |Cite
|
Sign up to set email alerts
|

Institutional and provider factors impeding access to trauma center care

Abstract: Epidemiologic study, level II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 16 publications
0
18
1
Order By: Relevance
“…The problem is particularly acute at non-trauma centers, where fewer than 30% of severely injured patients are transferred as recommended by clinical practice guidelines. 21 22 23 24 25 Our prior experimental and observational work suggests that heuristics play an important role in under-triage. 26 27 We selected one promising method of recalibrating heuristics—narrative engagement—and developed a theoretically grounded intervention delivered through the platform of a video game.…”
Section: Introductionmentioning
confidence: 99%
“…The problem is particularly acute at non-trauma centers, where fewer than 30% of severely injured patients are transferred as recommended by clinical practice guidelines. 21 22 23 24 25 Our prior experimental and observational work suggests that heuristics play an important role in under-triage. 26 27 We selected one promising method of recalibrating heuristics—narrative engagement—and developed a theoretically grounded intervention delivered through the platform of a video game.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, CT scans at the initial facility were strongly protective against SO, corroborating a Canadian study which reported that nontrauma centers with CT scanners, in addition to general surgery services, had decreased overall rates of transfer to trauma centers. 13 We sought to confirm that the conclusions we reported within our previous study are applicable at the national level and to explore new factors not previously analyzed. The long-term goal of this research is to facilitate the development of targeted strategies to reduce the SO rate and thereby help alleviate the burden of SO on tertiary center resources and improve patient care.…”
Section: Introductionmentioning
confidence: 72%
“…This is consistent with an earlier study of Canadian hospitals and our prior state-level study. 13,15 There may be several explanations for the observed effect. A negative head CT for any pathology may enhance provider comfort in discharging the patient, and patients identified as transfer candidates may have had their imaging studies completed at the receiving facility.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, between 30 and 40 % of patients with moderate-to-severe injuries still receive treatment at non-trauma centers ( under-triage) [57]. The problem amplifies among the cohort evaluated by physicians at non-trauma centers—70 to 80 % of whom are under-triaged [8, 9]. …”
Section: Introductionmentioning
confidence: 99%